2022
DOI: 10.1021/acs.jpclett.2c01873
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Protects the Liquid-Ordered Phase of Raft Model Membranes from the Destructive Effect of Ionic Liquids

Abstract: Ionic liquids (ILs), although being a class of promising green solvents, have received many reports on the toxicity to living organisms. In this work, aiming at elucidating the disruptive effect of ILs to cell membrane lipid rafts, we investigated the effect of three 1-octylimidazolium-based ILs on the properties of the liquid ordered phase (L o , a commonly used lipid raft model) of egg sphingomyelin (SM)-cholesterol model membrane. We found that, in the absence of cholesterol, a very low IL:SM molar ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
5
16
0
Order By: Relevance
“…The surface pressure–area isotherm generated by a Langmuir trough is useful for studying interactions among amphiphilic molecules that form a single molecular layer at the air–water interface. ,, Researchers have adopted this approach to understand the thermodynamics of the interaction of ILs with lipids. ,, It has been reported that the polar head group and hydrophobicity of lipids and the nature of anions and cations of ILs along with the pH of the environment play significant roles in this interaction. , Apart from electrostatics and van der Waals interactions, the thermodynamic state of a lipid in the membrane is important here . Further, as mentioned in the Introduction section, the interaction between a lipid and an IL may highly be influenced by the presence of other membranous component, such as cholesterol. , In the present study, the respective isotherms are generated by plotting the surface pressure against the area per molecule, which is calculated by considering the number of molecules of lipid (single component), lipid and IL (two components), and lipid, cholesterol, and IL (three components). The area/molecule signifies the average area occupied by a single molecule either in its pristine form (lipid) or in a mixed system (two or three components).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The surface pressure–area isotherm generated by a Langmuir trough is useful for studying interactions among amphiphilic molecules that form a single molecular layer at the air–water interface. ,, Researchers have adopted this approach to understand the thermodynamics of the interaction of ILs with lipids. ,, It has been reported that the polar head group and hydrophobicity of lipids and the nature of anions and cations of ILs along with the pH of the environment play significant roles in this interaction. , Apart from electrostatics and van der Waals interactions, the thermodynamic state of a lipid in the membrane is important here . Further, as mentioned in the Introduction section, the interaction between a lipid and an IL may highly be influenced by the presence of other membranous component, such as cholesterol. , In the present study, the respective isotherms are generated by plotting the surface pressure against the area per molecule, which is calculated by considering the number of molecules of lipid (single component), lipid and IL (two components), and lipid, cholesterol, and IL (three components). The area/molecule signifies the average area occupied by a single molecule either in its pristine form (lipid) or in a mixed system (two or three components).…”
Section: Resultssupporting
confidence: 77%
“…65 Further, as mentioned in the Introduction section, the interaction between a lipid and an IL may highly be influenced by the presence of other membranous component, such as cholesterol. 61,62 In the present study, the respective isotherms are generated by plotting the surface pressure against the area per molecule, which is calculated by considering the number of molecules of lipid (single component), lipid and IL (two components), and lipid, cholesterol, and IL (three components). The area/ molecule signifies the average area occupied by a single molecule either in its pristine form (lipid) or in a mixed system (two or three components).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTT assay was performed to estimate the viability of HeLa cells on the addition of different ionic liquids, as described previously. 44 HeLa cells, seeded in a 96-well plate, were subjected to varying concentrations (0, 10,25,35,40,50,60,75,85,100,125,150, and 175 μM) of DILs in triplicates for a period of 24 h to evaluate their cytotoxicity. Stock solutions of all ionic liquids (10 mM) were prepared in the MEM with 10% FBS.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…As a result, DILs are relatively less toxic as compared to their monocationic counterparts carrying alkyl chains of comparable length . The toxicity of MILs correlates with their ability to interact and perturb the cellular membrane. ,, Several computational and experimental studies have been employed to study the mechanism of the interaction of monocations with the model phospholipid membranes. , However, the structural details of dication–membrane interaction and its correlation with ionic liquid toxicity are not well understood.…”
Section: Introductionmentioning
confidence: 99%